PELATIHAN PEMBUATAN OBAT TRADISIONAL BERBAHAN DASAR BUBUK BAWANG HITAM (Black Garlic ) DI DESA TANJUNG SEUMANTOH KECAMATAN KARANG BARU KABUPATEN ACEH TAMIANG - Ekariana S. Pandia; Abdul L Mawardi; Tri Mustika Sarjani (LPPM dan PM Universitas Samudra, 2020)
Utilization of herbal plants for alternative medicine is very much studied now. One of the uses of kitchen ingredients that are often found is garlic. Utilization of garlic as an alternative treatment is often done and the last is the use of garlic into garlic onion. Black garlic is fermented garlic with a temperature of 700 – 800 C. Which is left for more than 12 days. The discovery began in China and Korea, which has benefit beyond the original garlic. Black garlic have stronger antioxidants than garlic. Sulfur amino acid compounds which are anti-cancer and neutropic antioxidants. This service aima to provide training for housewives in Tanjung Seumantoh karang Baru Village, Aceh Tamiang to utilize the spices which are often used as food additives in order to make traditional medicines that provide economic value, so they can help the community’s economy itself. By making black garlic powder, the selling price is better and more durable than direct consumption black garlic. The activity lasted for 6 months from April to October 2019 . with this community service program, it became a solution to the problems faced by housewives as a source of supplementary household economics and to find alternative